(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2017)
We can call digital revolution as serendipity which has changed the whole concept of technology from what it was 10 years back. Knowingly or unknowingly, many prodigious discoveries have been made which has positively contributed towards the advancements of the society that we live in. Not trite but original, at times detrimental but mostly constructive, not frivolous but vigorous, this also defines indomitability of digital revolution. In contemplation, I had an epiphany that the preponderance of Demonetization has changed the whole structure of the market. There are myriad of questions brimming in the mind of Indian citizens. Enough we have heard about the positive and negative aspect of it but did we ever pause and think what exactly it has given to our society? It has brought our society to a whole new digital world. I can indubitably say that the catalytic impact on the development of a “cashless economy” will hasten broader governmental efforts to reduce tax evasion and black market transaction. Introduction of newest substitute of traditional payment method i.e. E-money has now become a part of the monetary aggregates from the balance sheet of central banks. The movement towards a global economy, merging operational boundaries & unprecedented explosion of free trade/exchange worldwide has brought about massive opportunities to develop newer tools, instruments and methodologies in the fields of strategic management & entrepreneurship. With the introduction of E-money the operational policies, the regulatory system, the degree of integration in the global economic and financial markets and procedures of many organizations has radically changed in order to give lucrative results.